Environmental pollution of dam water in Daraa Governorate - Saeed , Abraham; Al-Salama, Amani Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Water plays a very important role in the development and development of civilizations and for human needs in all fields. Since Syria is located in the semi-arid region and suffers from lack of resources, it is necessary to establish dams to store water behind these dams to take advantage of its water. As for the pollution of the dams, the exposure of the region for long droughts led to deterioration of water quality. Are vulnerable to pollution due to lack of rainfall and lack of sufficient water collection in addition to being exposed to pollution from sewage and agricultural in the human communities near the dams. And perhaps rain water flow during the run in the territories adjacent to the path of nutrition in addition to self-pollution in these dams due to the death of algae and the phenomenon of explosionWhich causes their inflation after the death to form oils, which gives the interaction with chlorine taste is not desirable for water The real problem in the pollution of the water of these dams can not stop the natural pollution, especially the arrival of nutrients and phosphorus and organic materials that reach the dam lakes as a result of passage in the agricultural land adjacent to the dam . Pollution from untreated sewage, agricultural and industrial sewage is one of the most dangerous types of pollution affecting humans if it results in diseases that may be deadly to humans if they are fed to polluted organisms. These pollutants are many types of bacteria and primates Swiming in areas contaminated with untreated wastewater may also result in the spread of skin diseases and epidemics such as fever and hepatitis